2022
DOI: 10.1186/s12891-022-05059-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of workplace upper extremity resistance exercises on function and symptoms of workers at a tertiary hospital: a randomized controlled trial protocol

Abstract: Background Work-related musculoskeletal disorders (WRMDs) are often caused by inadequate use of the musculoskeletal system during work. Evidence suggests that multimodal intervention through exercises, massage, education, and ergonomic guidelines reduces pain and symptoms in the neck and upper extremities and help to prevent musculoskeletal disorders. The purpose of this study will be to assess the additive effectiveness of a specific and individualized workplace strengthening exercise program … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Resistance strengthening exercises, muscle stretching, proprioception training, and massage have been shown to reduce fatigue and pain in the upper extremities of workers [ 41 ]. With other occupations, a systematic review of workplace interventions to prevent upper extremity pain found strong evidence for the use of resistance training and no benefit with office workstation adjustment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resistance strengthening exercises, muscle stretching, proprioception training, and massage have been shown to reduce fatigue and pain in the upper extremities of workers [ 41 ]. With other occupations, a systematic review of workplace interventions to prevent upper extremity pain found strong evidence for the use of resistance training and no benefit with office workstation adjustment [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies show that physical activity has a preventive effect and reduces the risk of musculoskeletal complaints [24]. Studies show that regular exercise has a measurable effect with carpal tunnel syndrome before and after endoscopic exercise, massage, education and ergonomic guidelines appears to be the best workplace strategy of preventing musculoskeletal disorders [27]. In addition, the important impact of working with a therapist is often emphasized by researchers.…”
Section: Exercises Protocol For Office Workers O R I G I N a L P A P E Rmentioning
confidence: 99%